(untitled) (LACCEI, 2024)
The generation of acid mine drainage (AMD) represents one of the main challenges that mining companies must deal with daily. Despite the success of conventional methods, some elements, such as arsenic, are difficult to remove, even under highly basic conditions, so new environmental remediation methods need to be explored. This work seeks to broaden the knowledge of heterogeneous UV photocatalysis, a technique that uses nanotechnology to remove toxic compounds, and it has already been successfully tested in organic solutions and wastewater however, its applications for acid mine water have been tiny explored in the literature. The results of experimental tests using AMD solutions obtained from the district of Hualgayoc, Cajamarca, in an environment irradiated by sunlight and ultraviolet light are summarized. They show an arsenic remotion greater than 87% at a pH of 2.5 under a concentration of 10% TiO2 after one hour of agitation and irradiation with ultraviolet light. This serves as a starting point for new research that favors the development and application of sustainable technologies in the mining industry.